Creativity in the Light of Edwin E. Gordon's Theory of Learning Music - Beata Bonna (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The article presents the most important assumptions of E.E. Gordon's theory of learning music concerning the development of creativity through improvisation, which is the most perfect manifestation of musical thinking. It focuses on describing concepts related to creativity, creation and creative activity. Particular attention was paid to the characteristics of musical creation and improvisation, the types of improvisation and methods for its development, as well as the methods for measurement and evaluation. In the Polish educational reality, creativity and improvisation do not occupy their rightful place. Indications arising from Gordon's theory of learning music can be an important reference point supporting their broader inclusion in the system of music education in Poland.